COMMUNICATION ASPECTS OF MANAGEMENT WORK ON THE BASIS OF LEADERSHIP - Haliuk , I. B.; Verbovska , L. S.; Stetsko , O. I. (The actual problems of regional economy development, 2022)
The article is devoted to defining the role of the leader and outlining the basic principles of building communication with the team in a changing environment. To achieve the goal of the research, the method of theoretical research, general logic and generalization method were used. The authors consider the peculiarities of the organization of internal communications at the enterprise in the context of changes, which are to identify specific functions that must be represented within these processes. The authors present the structure of communications in the organization, which is used in stable conditions of the enterprise. The specific functions of the management staff in providing the communicative component in the process of enterprise management are outlined. The tasks of the immediate team leaders, which they must perform in order to harmonize the communication processes within a separate unit, are highlighted. The advantages obtained in a situation of properly organized internal communication are presented. In the course of the research the specifics of the organization of communicative processes in the conditions of changes, especially unpredictable, for example, caused by quarantine restrictions, martial law, etc. are highlighted. It is determined that the role of the leader in ensuring emotional stability and balance of the team is crucial. As the situation of change requires responsible leadership - the leader professes the values ​​of the organization, ready to be an example for the team, creates conditions for a sense of team involvement, etc., the appropriate behavior of the leader Based on the study, the authors concluded that the main one is the understanding that effective internal communication allows you to form strong teams that are united by common values: responsibility, team spirit, integrity. It is determined that in the conditions of changes, internal communication should perform another function - supportive, the essence of which is to maintain emotional balance in the team and the implementation of which falls on the leader as the initiator of communication. Only such an approach will reduce resistance and reduce the level of tension in the team and make the process of adaptation to change less traumatic.